2016
DOI: 10.1002/hfm.20406
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Usability of a Virtual Training System for Assembly Operations within the Automotive Industry

Abstract: Virtual training systems deliver training within a virtual environment (VE) using virtual reality (VR) or augmented reality (AR) technologies. However, to be fully accepted as a valid tool for training within the automotive industry, evidence is required on the ability of these systems to deliver effective and efficient training to the relevant users. This paper aims to investigate the effectiveness and efficiency of the first prototype of the virtual training system (VTS) developed within the VISTRA (Virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 30 publications
0
34
2
Order By: Relevance
“…However, in contrast to our results, the authors found that HMD-based training led to fewer errors. Overall, our results do not reflect the promising prospect of VR portrayed by other researchers [23]. This contrast may be due to the richness of hands-on experience, which is very difficult to simulate in VR, and may present a great benefit to learning.…”
Section: Discussion Of Findingscontrasting
confidence: 97%
See 2 more Smart Citations
“…However, in contrast to our results, the authors found that HMD-based training led to fewer errors. Overall, our results do not reflect the promising prospect of VR portrayed by other researchers [23]. This contrast may be due to the richness of hands-on experience, which is very difficult to simulate in VR, and may present a great benefit to learning.…”
Section: Discussion Of Findingscontrasting
confidence: 97%
“…Arthur et al [1] define knowledge decay as "loss of trained [...] knowledge over extended periods of non-use". A series of studies have researched how different training methods influence the participants' retention of knowledge [5,15,20,23].Knowledge retention can be evaluated at varying intervals after training, ranging from instantaneously to more than 365 days later [1].…”
Section: Parameters For Comparing Training Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anastassova and Burkhardt (2009) discussed the benefits of AR as a tool to solve some typical training problems for automotive service technicians. The study by Langley et al (2016) also focused on the effectiveness of AR systems for training of users. Other position papers provided guidelines for AR implementation, either in general terms (Chimienti et al, 2010) or for the deployment of AR in the specific areas, e.g., assembly and remote maintenance (Haist, 2008).…”
Section: Conceptual Papersmentioning
confidence: 99%
“…During the training a guidance system provides multimodal cues, including voice recordings, textual instructions, highlights and animations, and haptic feedback [7]. To improve knowledge transfer, two levels of difficulty were implemented [10]: Beginner and Intermediate.…”
Section: Multimodal Guidance Systemmentioning
confidence: 99%